Energy transfer and wavelength tunable lasing of single perovskite alloy nanowire. (May 2020) - Tang, Bing; Hu, Yingjie; Lu, Jian; Dong, Hongxing; Mou, Nanli; Gao, Xinyu; Wang, Hu; Jiang, Xiongwei; Zhang, Long
Abstract: Single perovskite alloy nanowire capable of emitting lasing broadly and continuously is highly desirable for the miniaturization and integration of all-photonic devices. However, due to the limitation of a soft and dynamic crystal lattice and the synthesized strategy, single perovskite nanowire with single-band lasing emission is mostly observed. Here, we propose a solid-solid anion-diffusion process to construct single CsPbCl3-3x Br3x perovskite alloy nanowire with a widely tunable bandgap from 2.41 to 2.82 eV and a regularly geometrical structure. We realized a broadly and continuously tunable nanolaser from 480 to 525 nm in single CsPbCl3-3x Br3x nanowire, as different spots along the length serve as a gain medium and microcavity simultaneously. The kinetics and atomic-scale mechanism of solid-solid anion diffusion were analyzed by a quantitative study and theoretical calculations, giving a small activation energy of halide migrations. The dynamics of carrier transportations revealed the energy transfer in single CsPbCl3-3x Br3x alloy nanowire, that's why broadly tunable lasers are difficult to realize in single isolated nanowire. Our work proposes a new strategy to construct single perovskite alloy nanowire for achieving a broadly and continuously tunable laser, clarifies the mechanism and kinetics of anion diffusion in perovskite alloy nanowires. Graphical abstract: We realized a broadly and continuously wavlength-tunable lasers (480–525 nm) in single perosvkite alloy nanowire. An anion-diffusion process was proposed to construct the nanowire with a widely tunable bandgap (2.41–2.82 eV), the kinetics and atomic-scale mechanism of anion diffusion were analyzed. The carrier dynamics were systematically studied to clarify the energy transfer of single perovskite alloy nanowire. Image 1 Highlights: A broadly and continuously (480–525 nm) tunable laser is realized in single CsPbCl3-3x Br3x nanowire. Single CsPbCl3-3x Br3x nanowire with a widely tunable bandgap (2.41–2.82 eV) is realized via an anion-diffusion process. The kinetics and atomic-scale mechanism are clarified in theory and experiment. The energy transfer is revealed by time-resolved photoluminescence measurements in single nanowire.